2012
DOI: 10.1590/s1677-55382012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Second to fourth digit ratio: its relationship with core cancer volume and Gleason score in prostate biopsy

Abstract: ARTICLE INFO _________________________________________________________ ___________________Objective: To investigate the relationships between 2nd to 4th digit ratio (digit ratio) and prostate cancer detection rate and biopsy findings, including Gleason score. Materials and Methods:In 770 consecutive men aged 40 years or older that presented with lower urinary tract symptoms (LUTS), right hand 2nd and 4th digit lengths were measured prior to PSA determinations, DRE and transrectal ultrasonography (TRUS). Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
15
2
5
Order By: Relevance
“…In addition, the mean value of the females’ digit ratio was lower than that of males in our previous studies (0.952,19 0.97,20 0.951,58 and 0.94859. However, in one study conducted among 664 (332 males, 332 females) university students (mean age: male: 22.4 years, female: 21 years), the digit ratio in Korean men was significantly lower than that of Korean women (0.96 vs 0.97, P < 0.001) 60.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, the mean value of the females’ digit ratio was lower than that of males in our previous studies (0.952,19 0.97,20 0.951,58 and 0.94859. However, in one study conducted among 664 (332 males, 332 females) university students (mean age: male: 22.4 years, female: 21 years), the digit ratio in Korean men was significantly lower than that of Korean women (0.96 vs 0.97, P < 0.001) 60.…”
Section: Discussioncontrasting
confidence: 59%
“…Then, in a major cohort study in the United Kingdom, researchers have proposed that 2D:4D may be a simple marker of prostate cancer risk, with length of 2D greater than 4D suggestive of lower risk 9 . Another investigation in 2012, the Korean researchers found an association between 2D:4D, prostate cancer volume and Gleason score after investigating 770 men with lower urinary tract symptoms 38 . However, in 2013, one US study found lower right-hand digit ratios for African-Americans with prostate cancer in comparison to Caucasians, but no significant differences for Gleason scores 14 .…”
Section: Discussionmentioning
confidence: 97%
“…More recently, three studies have evaluated 2D:4D ratio and PCa diagnosis and severity [29,30,31]. A Spanish group found that patients with a left 2D:4D ratio >0.95 had a 4-fold risk of PCa diagnosis in biopsy [29].…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish group found that patients with a left 2D:4D ratio >0.95 had a 4-fold risk of PCa diagnosis in biopsy [29]. This finding was just the opposite of an Korean group study, which found an increased PCa detection in patients with a lower 2D:4D ratio in right hand [30]. An American group study did not find an association between 2D:4D ratio and PCa severity [31].…”
Section: Discussionmentioning
confidence: 99%